Risk factors for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP): antecedent events, lifestyle and dietary habits. Data from the Italian CIDP Database. (9th August 2019) - Doneddu, P. E.; Bianchi, E.; Cocito, D.; Manganelli, F.; Fazio, R.; Filosto, M.; Mazzeo, A.; Cosentino, G.; Cortese, A.; Jann, S.; Clerici, A. M.; Antonini, G.; et al.
Abstract : Background and purpose: The role of lifestyle and dietary habits and antecedent events has not been clearly identified in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods: Information was collected about modifiable environmental factors and antecedent infections and vaccinations in patients with CIDP included in an Italian CIDP Database. Only patients who reported not having changed their diet or the lifestyle habits investigated in the study after the appearance of CIDP were included. The partners of patients with CIDP were chosen as controls. Gender‐matched analysis was performed with randomly selected controls with a 1:1 ratio of patients and controls. Results: Dietary and lifestyle data of 323 patients and 266 controls were available. A total of 195 cases and 195 sex‐matched controls were used in the analysis. Patients eating rice at least three times per week or eating fish at least once per week appeared to be at decreased risk of acquiring CIDP. Data on antecedent events were collected in 411 patients. Antecedent events within 1–42 days before CIDP onset were reported by 15.5% of the patients, including infections in 12% and vaccinations in 1.5%. Patients with CIDP and antecedent infections more often had an acute onset of CIDP and cranial nerve involvement than those without these antecedent events. Conclusions: The results of this preliminary study seem to indicate that some dietary habits may influence the risk of CIDP and that antecedent infections may have an impact on the onset and clinical presentation of the disease.